UPDATING SMALL WORKING AREA STATISTICS MAPPING USING HIGH- RESOLUTION IMAGE DATA: A CASE STUDY TO FACILITATE POPULATION CALCULATION IN BATAM MUNICIPALITY, INDONESIA - Anurogo, Wenang; Annisa, Fitri; Wulandari, Dwi Anjen Setia; Bacut, Geubrina Tari; Aji, Satriya Bayu; Darmanto, Adi (JURNAL PENDIDIKAN ILMU SOSIAL, 2020)
The identification of the administrative area maps is done using the data from boundary mapping conducted by field workers. This mapping was carried out with a process of field survey and renewal of the position of the boundaries of the area. These regional boundaries will be processed by supporting applications (QGIS). Maps are simply presented as a description of the area of information placed in the form of territorial boundaries. This research aims to update the statistical data map used to calculate the population in the research area. The regional apparatuses (District, Sub District,) serve as a starting point for mapping processing and as information on the smoothness of the 2020 population census. The processing produces administrative boundary data that has been updated from the previous map in the form of gender and infrastructure (facilities and infrastructure), the number of residents per District, the area per District and the location of astronomical lines in the region. Based on the mapping identification results, there are several boundaries of the area whose position has been shifted due to two factors, namely changes by natural factors and changes by human activities as well as a discrepancy between Digital Maps and Analog Maps. Then it is necessary to map administrative areas that are in accordance with the application of satellite imagery (SW Maps) which are represented in vector format.